ANTI HYPERGLYCEMIC AND ANTI DYSLIPIDEMIC EFFECTS OF FLAX SEEDS (LINUM USITATISSIMUM) EXTRACT IN DIABETIC RATS MODEL - Jabbar Ahmed Qureshi; Zahida Memon; Kauser Ismail; Shanza Agha; Fizza Saher; Vanita Motiani (ziauddin University, 2024)
Background: Herbal medications, due to their various biologically active components and less toxic profile, have been popular amongst researchers since decades. One good example is Linum usitatissimum (Lu) commonly known as Flaxseeds. The aim of present study was to assess the anti hyperglycemic and anti dyslipidemic activities of ethanolic extract of flax seeds (Linum usitatissimum) in streptozotocin induced diabetic rat model. Methods: The ethanolic extract of flax seeds (Linum usitatissimum) at a dose of 200 mg/kg and 400mg/kg were given to the streptozotocin-induced diabetic rats for the period of 28 days. FBS, insulin, HbA1c, lipid profile and serum amylase were evaluated and were compared with positive and negative controls and standard drugs like Glimepiride 0.1 mg/kg b.w., Metformin 10mg/kg b.w. and Rosuvastatin 10mg/kg/day b.w. Results: Both doses of flax seeds 200 mg/kg and 400 mg/kg (Linum usitatissimum) extracts demonstrated significant (p<0.001) decrease in FBS of diabetic rats. Mainly Linum usitatissimum at the dosage of 400 mg/kg b.w. showed good efficacy in declining fasting blood glucose levels which was comparable with standard anti hyperglycemic drugs. Both doses of herbal extracts also showed significant decline in triglycerides, total cholesterol, and low-density lipoprotein (LDL-C), very low-density lipoproteins (VLDL-C), and serum amylase levels with prominent improvement in HDL-C levels in diabetic rats compared to positive controls. Conclusion: This study reveals that the flax seeds (Lu) at the dose of both 200mg/kg and 400mg/kg have noteworthy potential to reduce hyperglycemia and dyslipidemia associated with diabetes, therefore may be it is useful in the management of Type-2 diabetes mellitus.